The effect of fire on tree-ring width and tracheid dimensions of Pinus nigra - Keleş, Seray Özden; Ünal, Sabri (Walter de Gruyter GmbH, 2024)
Summary Forest fires play a significant role in the growth and development of trees because they can damage the phloem and cambium. Fire injury induces the formation of fire scars that can cause xylem dysfunction. The study area is located in Taşköprü, Kastamonu (Western Black Sea of Turkiye), where two forest fires occurred in 1957 and 2020. In this study, the effect of the 1957 fire on the tree-ring widths and tracheid dimensions of Pinus nigra trees was investigated. We measured tree-ring widths and tracheid dimensions of fire-scarred (FS) and unscarred (UF) trees during four different periods: the pre-fire period (1947–1956), fire event year (1957), and post–fire periods (1958–1967 and 2011–2020). In this study, UF trees showed almost 2.5–3 times wider tree–ring widths (TRWs) than FS trees. FS and UF trees also showed great variation in tracheid dimensions in the four different periods; the average tracheid diameter (TD), lumen area (TLA), and wall thickness (TWT) values increased significantly in UF trees compared to FS trees during the fire event and post-fire periods. The average TD, TLA, and average tracheid lumen diameter (TLD) decreased during the fire and post-fire years in the FS trees. In this study, we suggest that fire injury significantly affects the tracheid dimensional traits of FS Pinus nigra trees. Our results also suggest that although Pinus nigra trees experienced serious fire damage, they continued to grow but with a decrease in tracheid size.
Keywords: 15. Life on land